The Effect of Leverage on Asset Sales Between Financial Institutions - Das, Sonali (IMF Working Papers; Working Paper ;, 2017)
This paper analyzes how the leverage of financial institutions affects their demand for assets and the resulting value of transactions between financial institutions. The results show a positive relationship between buyer capital and the likelihood of buying assets, and between buyer capital and the value of the deal. That is, those institutions that are the least constrained in their ability to raise funding are those that demand assets and pay more for them. This result does not hold, however, for deposit-taking institutions that had access to several government programs designed to improve their liquidity position during the crisis of 2008.